2019
DOI: 10.1519/jsc.0000000000002798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6 Weeks of Different High-Intensity Interval and Moderate Continuous Training on Aerobic and Anaerobic Performance

Abstract: Cavar, M, Marsic, T, Corluka, M, Culjak, Z, Cerkez Zovko, I, Müller, A, Tschakert, G, and Hofmann, P. Effects of 6 weeks of different high-intensity interval and moderate continuous training on aerobic and anaerobic performance. J Strength Cond Res XX(X): 000-000, 2018-To provide practical data, we compared the training effects of 3 different programs, using a shuttle run stimulus, on aerobic and anaerobic performance, measured using the 20-m maximal shuttle run (Beep) test and 300-yd shuttle run, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…Cavar et al (5) found that 20MSFT could be improved to a greater extent in college-aged men by long high-intensity (~3 x 3 min work: rest ratios at 90-95% maximal shuttle-run speed…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cavar et al (5) found that 20MSFT could be improved to a greater extent in college-aged men by long high-intensity (~3 x 3 min work: rest ratios at 90-95% maximal shuttle-run speed…”
Section: Resultsmentioning
confidence: 99%
“…It could be expected that sprint interval training methods similar to that presented by Helgerud et al (16) and Cavar et al (5) would be more beneficial to enhancing 20MSFT performance. If recruits did not complete this type of training prior to academy, this could mean that while they may be aerobically conditioned, the capacity to sustain high-intensity efforts is less optimal (5,40). Indeed, this would have impacted the estimated V O2max derived from the 20MSFT, which was much lower than that for the 2.4-km run.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the ability to change direction could impact not just the 20MSFT, but job performance in tasks such as a foot pursuit as well (2). Highintensity running is also stressed in the 20MSFT, and this quality needs to be specifically trained (3). Developing high-intensity running would be beneficial for recruits given many of their job tasks demand high-intensity, externally-paced activity (16).…”
Section: Discussionmentioning
confidence: 99%
“…Programar correctamente estas sesiones de entrenamientos interválicos será muy importante si se quiere que el estímulo producido en los deportistas sea efectivo. En la actualidad existen dos métodos muy comunes en la programación de la intensidad en los entrenamientos de HIIT: % FCmáx o una velocidad de referencia (Buchheit y Laursen, 2013a y b; Cavar et al, 2019;Impellizzeri et al, 2006;McMillan, Helgerud, Macdonald y Hoff, 2005;Rabbani y Buchheit, 2015). Sin embargo, no son los dos métodos igual de fiables.…”
Section: Hiit (High Intensity Interval Training)unclassified